2004
DOI: 10.1002/cb.158
|View full text |Cite
|
Sign up to set email alerts
|

Building the buzz in the hive mind

Abstract: holds an MBA from the McCombs School of Business and is the Managing Director of Brandeverything, a marketing consultancy based in California. AbstractWhat is the secret to buzz marketing? Buzz marketing is defined as the amplification of initial marketing efforts by third parties through their passive or active influence. This powerful conceptual framework is illustrated in this paper with practical information on how to build the buzz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
19

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 1 publication
1
58
0
19
Order By: Relevance
“…The viral marketing is a current phenomena and has been discussed in the literature under a variety of different terms such as buzz marketing or viral advertising (Thomas, 2004;Kaplan y Haelein, 2011), stealth marketing (Kaikati & Kaikati, 2004;Kaplan and Haelein, 2011) and word-of-mouth marketing (Kozinets et al, 2010;Kaplan and Haelein, 2011). The term of viral marketing comes from an article written by Jeffrey Rayport (1996) of Harvard Business School and published in the magazine Fast Company as "The Marketing Virus".…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…The viral marketing is a current phenomena and has been discussed in the literature under a variety of different terms such as buzz marketing or viral advertising (Thomas, 2004;Kaplan y Haelein, 2011), stealth marketing (Kaikati & Kaikati, 2004;Kaplan and Haelein, 2011) and word-of-mouth marketing (Kozinets et al, 2010;Kaplan and Haelein, 2011). The term of viral marketing comes from an article written by Jeffrey Rayport (1996) of Harvard Business School and published in the magazine Fast Company as "The Marketing Virus".…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…DOI: http://dx.doi.org/10.1108/JRME-07-2015-0039 (Bjerke & Hultman, 2002). Some entrepreneurial marketing tactics include word of mouth marketing (Keller, 2007), viral marketing (Hinz, Skiera, Barrot, & Becker, 2011) and buzz marketing (Hausmann, 2012;Thomas, 2004). While analysing the marketing practices of successful entrepreneurs, Stokes (2000) found that they tend to serve a small base of customers and expand based on resource availability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…No obstante, en los estudios analizados es mucho más habitual hacer referencia al WOM (word of mouth) y al "buzz marketing" (Thomas, 2004, p. 64 y Smith, Coyle, Lightfoot y Scott, 2007; de nuevo, diferentes conceptos hacen referencia a técnicas de comunicación muy similares. Las investigacio- …”
Section: Revisión Teórica 1 Revisión De Los Estudios De Técnicasunclassified
“…(Thomas, 2004;Smith, Coyle, Lightfoot y Scott, 2007;Carl, 2006). Según esta hipótesis, los atributos que caracterizan a estas técnicas están muy próximos entre sí, poniendo en duda la diferenciación entre ellas, y revelando una simplificación del concepto.…”
Section: H1unclassified